Priorities and factors influencing furniture preference of first-time Filipino homeowners when purchasing in physical stores - Miguel, Annika oelle S.; Taluban, Joseph G. (Quezon City University of the Philippines Diliman, 2023)
Furniture is considered a long-term investment (Guzel, 2020), however, its qualities, specifications, and other important aspects are often neglected due to a discrepancy in the homeowner’s budget and income. The study made an attempt to determine and analyze the factors (personal, economic factors, and furniture criteria), and general considerations, that influenced the priorities and preferences in the different aspects of furniture design of first-time homeowners when purchasing furniture. Moreover, the study identified what aspects of home furniture design are preferred by first-time homeowners. The study used a qualitative research design, while a self-administered online survey form was used to gather the data. The respondents range from 25-35 years-old, Middle-Class Filipinos who are first-time homeowners living in Metro Manila. First-time homeowners are characterized by those who have been homeowners for less than or exactly five years and are either live-in partners, newlyweds, married, siblings, or starting-out families. The findings revealed that modern-style furniture, knockdown furniture, bedframe and mattress, and durable and comfortable furniture are aspects preferred and prioritized by first-time homeowners. The study’s findings and results led to the conclusion that despite having different external factors such as income, budget, and type of household, the general preference and priorities of first-time homeowners are furniture that are reasonably-priced in relation to its durability and comfort. To expound on this, first-time homeowners are willing to compromise on other criteria of the furniture, such as design and manufacturing type, to suit their budget. The results of this study will benefit the Philippine furniture industries, as they can explore different manufacturing types that can be at par with the emerging markets and develop Philippine-centric furniture designs.
Thesis
Includes bibliographical references (pages 127- 132)
Keywords: Furniture design -- Philippines; Consumers' preferences -- Philippines; Furniture industry and trade -- Philippines